Knowledge and Awareness of Employees about the Products and Activities of Islamic Banks to get the Job and Promotion in Bangladesh (Feni University Journal, 2026)
This study aims to analyze the knowledge and awareness of employees about the products and activities of Islam for getting jobs and promotions in Bangladesh. There are a total of ten full-fledged Islamic banks and Islamic windows in almost every commercial bank in Bangladesh. People from different educational backgrounds are servicing Islamic banks and Islamic windows of commercial banks. The success and competitive advantage of Islamic banking largely depend on the knowledge and awareness of its employees regarding the products and principles of Islamic banking. In this study, a random sampling method was used to collect 80 responses through a structured questionnaire from three out of ten Islamic banks. This study aims to show the knowledge of different products, principles, and aspects of Islamic banking that are related to employees’ performing Islamic banking activities. In part I, this study revealed that 70% have answered both general and Islamic knowledge required in the recruitment exam, 56% have answered supervisory authority supervises Islamic banking shariah, 79% have answered depositor’s profit depends upon the profit of the bank, 63% have been answered both general and Islamic knowledge require in promotion, 59% have been answered they strongly agree that bank maintain Islamic Shariah in its all transactions and 65.4% of the respondents have proper knowledge and 34.6% have not proper knowledge. In part II, maximum responses are optimistic that the banker possesses knowledge about bank principles, activities, and products.FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (63-82)